2020
DOI: 10.21206/rbas.v10i1.9281
|View full text |Cite
|
Sign up to set email alerts
|

Invertebrados Edáficos Em Culturas De Verão E Inverno No Noroeste Do Rio Grande Do Sul

Abstract: A biota edáfica apresenta importância fundamental nos processos naturais. O clima, os tiposde culturas utilizadas e as práticas agrícolas adotadas podem ser limitantes para a diversidade biológica dacomunidade desses invertebrados. A região noroeste do Rio Grande do Sul é uma das principais produtorasde grãos do Estado, entretanto, estudos avaliando a qualidade da biota edáfica são escassos nestes cultivos.Objetivou-se identificar os invertebrados edáficos em duas épocas sazonais distintas em áreas agrícolascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
0
1
Order By: Relevance
“…The loss of vegetal cover reduces the population and variability of species of springtails (Loranger et al, 1998), on the other hand, layers of vegetal cover favor the abundance of springtails (Jandl et al, 2003), due to better survival conditions (Moço et al, 2005), since the vegetal cover serves as a shelter for these organisms (Baretta et al, 2003) and the straw provides food for most organisms that live in the soil (Silva et al, 2006(Silva et al, , 2013, these vegetal cover benefits could explain the greater springtail amounts in the treatments with higher remaining straw, in accordance with the correlation found when treatment 2 was removed. Lucero et al (2020), when evaluating the abundance of soil organisms with five different vegetal coverings, found that springtails were the most abundant organisms in the area with wheat cover and in the turnip/ryegrass consortium, differing from the results found in this study, since the smallest populations of springtails occurred when the predecessor crop was wheat (T2). However, when analyzing the history of predecessor crops to soybean, there is a greater application of phytosanitary products in the wheat crop, mainly fungicides (three applications of Nativo® + Mancozeb®).…”
Section: Resultscontrasting
confidence: 99%
“…The loss of vegetal cover reduces the population and variability of species of springtails (Loranger et al, 1998), on the other hand, layers of vegetal cover favor the abundance of springtails (Jandl et al, 2003), due to better survival conditions (Moço et al, 2005), since the vegetal cover serves as a shelter for these organisms (Baretta et al, 2003) and the straw provides food for most organisms that live in the soil (Silva et al, 2006(Silva et al, , 2013, these vegetal cover benefits could explain the greater springtail amounts in the treatments with higher remaining straw, in accordance with the correlation found when treatment 2 was removed. Lucero et al (2020), when evaluating the abundance of soil organisms with five different vegetal coverings, found that springtails were the most abundant organisms in the area with wheat cover and in the turnip/ryegrass consortium, differing from the results found in this study, since the smallest populations of springtails occurred when the predecessor crop was wheat (T2). However, when analyzing the history of predecessor crops to soybean, there is a greater application of phytosanitary products in the wheat crop, mainly fungicides (three applications of Nativo® + Mancozeb®).…”
Section: Resultscontrasting
confidence: 99%
“…A sensibilidade dos organismos à oferta de alimentos reflete a importância dos resíduos orgânicos aplicados e dos resíduos vegetais da cultura antecessora. Neste caso, o milho, possui elevada relação C:N e sua decomposição é lenta, resultando em ambiente favorável para a fauna edáfica (Lucero et al, 2020). Desta forma, a redução da abundância total de organismos, como observado na 3ª coleta, pode ser resultante da menor oferta de alimento e de um hábitat menos favorável para os artrópodes (Rodrigues et al, 2016), pois as plantas do feijoeiro foram retiradas da área experimental no momento da colheita, procedendo em menor acúmulo de resíduo vegetal sobre a superfície do solo.…”
Section: Resultsunclassified
“…Os grupos mais expressivos coletados nesta época foram Diptera (25,9%), Acarina (25,5%) e Coleoptera (16,7%). No grupo Diptera, por sua vez, não foi encontrada diferença estatística entre os tratamentos da 3ª coleta, segundoLucero et al (2020) este grupo se apresenta de forma temporária no solo e não apresenta funcionalidade conhecida, no entanto, foi o grupo mais expressivo em todos os tratamentos desta coleta.…”
unclassified
“…Covering and incorporating of soil organic matter provide habitat and food for fauna, preserving and improving the diversity and richness of invertebrates. In addition, it increases infiltration and water retention in soil, improves soil aggregation, reduces erosion and loss of organic matter, and provides nutrients for plants (WU & WANG 2019;LUCERO et al 2020). However, poorly managed soil negatively impacts in habitat, richness and diversity of soil fauna, which undermines ecosystem services fundamental to soil health and agricultural activity (JIANG et al 2018;WU & WANG 2019;LUCERO et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it increases infiltration and water retention in soil, improves soil aggregation, reduces erosion and loss of organic matter, and provides nutrients for plants (WU & WANG 2019;LUCERO et al 2020). However, poorly managed soil negatively impacts in habitat, richness and diversity of soil fauna, which undermines ecosystem services fundamental to soil health and agricultural activity (JIANG et al 2018;WU & WANG 2019;LUCERO et al 2020). Among the impaired activities are aeration, aggregation and soil structuring, fragmentation and decomposition of organic matter, cation exchange capacity and nutrient cycling (DOMÍNGUEZ et al 2018;LUCERO et al 2020).…”
Section: Introductionmentioning
confidence: 99%